PEMBUKTIAN YANG DILAKUKAN PENUNTUT UMUM DALAM TINDAK PIDANA PERSETUBUHAN DENGAN ANAK - Giovanny Andreana Christya; Muhammad Rustamaji (Sebelas Maret University, 2021)
This study aims to analyze whether the evidence by the public prosecutor in the criminal case of sexual intercourse with a child based on Decision Number 37/Pid.Sus/2022/Pn.Krg is in accordance with Article 184 of the Criminal Procedure Code. This research is included in normative or doctrinal legal research that is prescriptive and applied. This study uses a case approach. In order to collect legal materials in this study, literature study techniques were used by collecting written information from legal materials, which consisted of primary legal materials and secondary legal materials. After obtaining the legal material, an analysis is carried out using the deductive syllogism method. The results of this study indicate that the evidence carried out by the public prosecutor is in accordance with Article 184 of the Criminal Procedure Code because it has submitted valid evidence according to law, namely witness statements, letters, statements of the defendant accompanied by supporting evidence to prove that the defendant is guilty of committing the crime of sexual intercourse with a child . This study aims to analyze whether the evidence by the public prosecutor in the criminal case of sexual intercourse with a child based on Decision Number 37/Pid.Sus/2022/Pn.Krg is in accordance with Article 184 of the Criminal Procedure Code. This research is included in normative or doctrinal legal research that is prescriptive and applied. This study uses a case approach. In order to collect legal materials in this study, literature study techniques were used by collecting written information from legal materials, which consisted of primary legal materials and secondary legal materials. After obtaining the legal material, an analysis is carried out using the deductive syllogism method. The results of this study indicate that the evidence carried out by the public prosecutor is in accordance with Article 184 of the Criminal Procedure Code because it has submitted valid evidence according to law, namely witness statements, letters, statements of the defendant accompanied by supporting evidence to prove that the defendant is guilty of committing the crime of sexual intercourse with a child.Keywords: evidence, child intercourse